2023
DOI: 10.3390/ijms24032192
|View full text |Cite
|
Sign up to set email alerts
|

GxxxG Motif Stabilize Ion-Channel like Pores through Cα―H···O Interaction in Aβ (1-40)

Abstract: Aβ (1-40) can transfer from the aqueous phase to the bilayer and thus form stable ion-channel-like pores where the protein has alpha-helical conformation. The stability of the pores is due to the presence of the GXXXG motif. It has been reported that these ion-channel-like pores are stabilized by a Cα―H···O hydrogen bond that is established between a glycine of the GXXXG sequence of an alpha-helix and another amino acid of a vicinal alpha-helix. However, conflicting data are reported in the literature. Some au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Compared with other energy storage methods, hydrogen energy storage has the following four obvious advantages: 1 in the new energy absorption, the advantages of hydrogen storage over other types of energy storage in terms of discharge time (hours to quarters) and capacity scale (100GW) are obvious,in terms of economies of scale of energy storage, as storage time increases [5][6][7][8] , as the marginal value of energy storage systems decreases, the total affordable cost will also decrease, with the cost of large-scale hydrogen storage being an order of magnitude lower than that of electricity storage, hydrogen storage can be carried out by means of long-tube trailers, pipeline transmission, natural gas mixing with hydrogen [9][10][11][12][13][14][15] , ultra-high voltage transmission-hydrogen production at the receiving end and liquid ammonia, etc. , compared with large-scale energy storage technologies such as pumped storage and Compressed air storage, hydrogen storage does not require specific geographical conditions and does not destroy the ecological environment as depicted is table 1.…”
Section: Frequency Modulation Characteristics Of Hydrogen Energy Storagementioning
confidence: 99%
“…Compared with other energy storage methods, hydrogen energy storage has the following four obvious advantages: 1 in the new energy absorption, the advantages of hydrogen storage over other types of energy storage in terms of discharge time (hours to quarters) and capacity scale (100GW) are obvious,in terms of economies of scale of energy storage, as storage time increases [5][6][7][8] , as the marginal value of energy storage systems decreases, the total affordable cost will also decrease, with the cost of large-scale hydrogen storage being an order of magnitude lower than that of electricity storage, hydrogen storage can be carried out by means of long-tube trailers, pipeline transmission, natural gas mixing with hydrogen [9][10][11][12][13][14][15] , ultra-high voltage transmission-hydrogen production at the receiving end and liquid ammonia, etc. , compared with large-scale energy storage technologies such as pumped storage and Compressed air storage, hydrogen storage does not require specific geographical conditions and does not destroy the ecological environment as depicted is table 1.…”
Section: Frequency Modulation Characteristics Of Hydrogen Energy Storagementioning
confidence: 99%
“…Multiscale molecular dynamics simulations of Aβ40 inserted into a POPC membrane revealed that the peptide selfassemble into a truncated cone-shape aggregate, causing a change in membrane curvature. 104 These aggregate exhibited ion-channel-like pores, facilitating the passage of water and ions across the bilayer (Figure 6A). This phenomenon is explicable through the frustrated-helix model, which attributes the change in bending radius to electrostatic repulsions among exposed hydrophilic amino acids.…”
Section: Pores Through Cα-h•••o Interactionmentioning
confidence: 99%
“…However, conflicting viewpoints exist in the literature regarding the stabilizing function of the GxxxG motif. Multiscale molecular dynamics simulations of Aβ40 inserted into a POPC membrane revealed that the peptide self-assemble into a truncated cone-shape aggregate, causing a change in membrane curvature . These aggregate exhibited ion-channel-like pores, facilitating the passage of water and ions across the bilayer (Figure A).…”
Section: Gxxxg Motif Stabilizes Ion Channel Like Pores Through Cα―h··...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, glycine residues in the GxxxG motif facilitate dimerization of α-helices in a large number of membrane proteins 38 , including the Aβ amyloid polypeptide 39 . As in PPII helical protein domains rich in glycine, Cα-H··O=C interactions have been reported to form in GxxxG motifs in the Aβ amyloid polypeptide and impact pathology 40 . Moreover, Cα-H··O=C H-bonds formed by this motif can also affect the α-helix – α-helix packing angle and α- helical stability in model α-helices assembled in membrane lipids 41 .…”
Section: Introductionmentioning
confidence: 99%